MECHATRONIC SYSTEM FOR THE PROMOTION OF PHYSICAL ACTIVITY IN PEOPLE WITH MOTOR LIMITATIONS - Pereira, Leandro (2018)
This work presents the initial step of the development of a mechatronic system that aims to promote physical activity in people with motor limitations. This mechatronic system consists of a stationary bike similar to the current gym bikes, with the difference of having a didactic component. The didactic component presents the integration of a game that simulates a paramotor in which the speed of pedalling allows the player to move up and down, while the position of the arms will allow the movement to the left and to the right in the game scenario. The model under study also presents the versatility of being able to ergonomically adjust to any person and to adjust the load for both upper and lower limbs. In this paper it is also detailed some aspects of the mechatronic system design, such as: modelling, study of materials and sensors, study of possible exercises, to be performed, and the development of the game scenario.